Perancangan Study Pod pada Area Publik Universitas Kristen Petra - Santoso, Brilliant Natalia (Intra, 2015)
A conducive study area is a need of students, especially in Petra Christian University. But often the given facility by the university is still cannot fulfill the need of their students. The facility that is needed for a study area is study pod. Study pod is a private space that can be used by university students and staffs to do their academic activities in the public area. These activities include learning, discussion, and browsing. The study pod design is made under the questionnaire survey and site observation, the selected location analysis, concept design alternates, designing and making prototype. Study pod is designed to have an ease of transfer, light, and flexible. Therefore, study pod uses a knock down system to fulfill the mentioned criteria. Study pod is one of the effort to fulfill the learning needs of Petra Christian University students to be facilitated in a comfortable means.